The Influence of Management Control Systems on the Financial Performance of Hospitals - Asaari, Masagus; Madjid, Suhirman (Santoso Academy Network, 2024)
The financial performance of a hospital largely determines the service quality of a hospital. The hospital's financial performance requires a hospital management control system consisting of structures and processes. This study aims to determine whether the Management Control Structure and Management Control Process influence the financial performance of Hospitals in the Municipality of Bogor and Bogor Regency for the 2016 period. This type of research is explanatory research; the data sources are primary and secondary data. Primary data collection techniques using questionnaires and secondary data collection with documentation. This study used a population of 16 hospitals in the Municipality and Bogor Regency. The analysis used is hypothesis testing, with the data analysis method used is Path Analysis. The results showed that the Management Control Structure and Management Process had a positive direct effect, either partially or simultaneously, on the Financial Performance of Hospitals in Bogor Municipality and Bogor Regency.